Comparing Journalism Cultures in Latin America: The Case of Chile, Brazil and Mexico - Mellado-Ruiz, C (2012)
Based on interviews with 300 journalists in Chile, Brazil and Mexico, this article describes similarities and differences in their professional cultures. Two competing conceptual explanations are tested: the dominance of political structures, levels of press freedom and the size and concentration of media ownership vs the predominance of political cultures and political parallelism. Although the study provides some evidence in favour of the second scenario - overall in terms of the institutional roles supported by the journalists - neither of the two explanations can fully account for the differences between the countries. Meanwhile, the epistemological and ethical views of the journalists seem to be trapped in contesting terrains of ambiguity, where organizational, media routines and individual factors override country differences. © The Author(s) 2012.